Comprehensibility of gender-fair language in German-language video lectures - Friedrich, Marcus C. G.; Krenz, Bianca (Frontiers in Psychology, 2025)
In many languages, it is common to use masculine-only forms when all genders are meant or gender is irrelevant to the actual statement. This practice is criticized for making women and members of other genders, their achievements and interests, less visible. Gender-fair language is intended to represent all genders equally. Recently introduced forms such as the glottal stop and the gender star are intended to also represent people outside the male-female dichotomy on the linguistic surface. However, it is often argued that gender-fair language would make texts less comprehensible and less aesthetically appealing. The critics' assumptions were tested in an experiment with 272 participants. Subjects watched a screencast on self-regulated learning and were randomly assigned to either a version using masculine-only forms or a version using the glottal stop and the gender star. Subsequently, participants rated the comprehensibility and aesthetic appeal of the video they had watched. Structural equation models show no statistically significant influence of the use of genderfair language on the comprehensibility (β = -.13) or the aesthetic appeal (β = -.16) of the videos. The critics' assumptions are therefore not supported. But further studies are needed, especially regarding the corresponding singular forms and with non-academic participants.